Rapid Design of 3D Reflectarray Antennas by Inverse Surrogate Modeling and Regularization - Koziel, Slawomir; Belen, Mehmet Ali; Caliskan, Alper; Mahouti, Peyman (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
Reflectarrays (RAs) exhibit important advantages over conventional antenna arrays, especially in terms of realizing pencil-beam patterns without the employment of the feeding networks. Unfortunately, microstrip RA implementations feature narrow bandwidths, and are severely affected by losses. A considerably improved performance can be achieved for RAs involving grounded dielectric layers, which are also easy to manufacture using 3D printing technology. Regardless of the implementation details, a practical bottleneck of RA design is the necessity of independent adjustment of a large number of unit cells, which has to be carried out using full-wave electromagnetic (EM) simulation models to ensure reliability. The associated computational costs are extraordinary. A practical workaround is the incorporation of surrogate modeling methods; however, a construction of accurate metamodel requires a large number of training data samples. This letter introduces an alternative RA design approach, where the unit cells are adjusted using an inverse surrogate model established with a small number of anchor points, pre-optimized for the reference reflection phases. To ensure solution uniqueness, the anchor point optimization involves regularization, here, based on the minimum-volume condition for the unit cell. The presented approach reduces the computational cost of RA design to a few dozens of EM analyses of the cell. Several demonstration examples are provided, along with an experimental validation of the selected RA realization.
Keywords: Reflection; Computational modeling; Costs; Optimization; Inverse problems; Reflector antennas; Computational efficiency; Antenna design; reflectarrays; surrogate modeling; inverse Modeling; EM-driven design; regularization; BROAD-BAND REFLECTARRAY; ELEMENT; Computer Science; Engineering; Telecommunications